(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
This study was aimed to evaluate the efficiency of three protein level feeds on the fingerlings production of riverine endangered Notopteruschitala (Hamilton, 1882) for a period of two months in ponds. Chital fry (Initial wt, 5.6±0.19 g) were randomly stocked at the rate of 7410 per hector. Feeding trials were conducted under 3 treatments (T1: feed contains 35% protein, T2: feed contains 30% protein, T3: feed contains 25 % protein) each with 3 replications. No significant (P<0.05) difference was observed for all the water quality parameters among the treatments. A suitable range of water quality parameters (temperature, water transparency (cm)), dissolved oxygen (mg/l), pH, alkalinity (mg/l), ammonia) were recorded with the environment of experimental ponds. The treatment had significant effects on weight gain, ADG, SGR among treatments. Highest weight gain (19.31 ± 0.23 g) was observed in T1, lowest (13.96 ± 0.15 g) in T3. SGR (1.65±0.02) and ADG (0.18±0.005) were significantly (P<0.05) highest in T1 followed by T2 and T3. The N chitala exhibited highest survival rate (96.66%) in T1 than T2 followed by T3 (88.89 %). The best FCR value (3.02±0.09) was recorded in treatment T1 with 35% protein contain feed. Relatively, highest benefits (138690±175.36 BDT/ha) were found from treatment T1 compared to other treatments. Similarly, the cost benefit ratio was highest in T1 (1:1.23) and lowest in T3 (0.95). Findings indicated that treatment T1 (35% protein containing feed) was found best in terms of growth, production and economics of N. chital for fingerling production in ponds. Res. Agric., Livest. Fish.7(3): 553-563, December 2020